Diseño cinemático de un robot paralelo 2-PRR - Durango Idárraga, Sebastián; Delgado Martínez, Mariline C.; Álvarez Vargas, César A.; Flórez Hurtado, Rubén D.; Flórez Ruiz, Manuel A. (Scientia et Technica, 2020)
In civil construction Abstract— This paper presents a dimensional synthesis for a 2-PRR planar parallel robot with a structural plane of symmetry. This robot can achieve the translation of the moving platform without changing the orientation, being useful for applications that require controlled positions with high rigidity. Because the performance of parallel robots is highly sensitive to their geometric parameters, many methodologies to state the dimensional synthesis has been developed. We used the method of Parameter - Finiteness Normalization Method (PFNM) to state the dimensional synthesis using Global Condition Index (GCI) and workspace ( ) design atlases. For the two, GCI and , designed atlases, it is not possible to maximize one of the indexes without diminishing the other one, which represents a design compromise. Also, we remark singular configurations that are coming from specific geometry or limit positions. The complete dimensional synthesis is also presented.